Corrosion fatigue and microstructural characterisation of Type 316 austenitic stainless steels tested in PWR primary water. (February 2018) - Mukahiwa, K.; Scenini, F.; Burke, M.G.; Platts, N.; Tice, D.R.; Stairmand, J.W.
Graphical abstract: Highlights: High sulphur content improves corrosion fatigue crack growth resistance when strain rates are low. Crack growth is crystallographic during enhanced crack growth and non-crystallographic during retardation. Micro-cleavage cracking occurred after the crack-tip had advanced. Evidence suggests that enhanced crack growth was caused by cathodically-produced hydrogen. Abstract: Fatigue crack growth experiments have been performed on high and low sulphur Type 316 austenitic stainless steel specimens in simulated Pressurised Water Reactor primary coolant environments and evaluated via microstructural characterisation techniques to further the understanding of the mechanistic behaviour. At relatively high loading frequencies, the enhanced crack growth for both specimens appeared to be crystallographic and associated with slip localization. However, when the loading frequency was decreased, the crack growth rates for the low S specimen increased, whereas the high S specimen exhibited retarded crack growth and the crack path was no longer crystallographic.